Accountable Care Organizations and Prostate Cancer Care. Issue 6 (November 2017) - Hollenbeck, Brent K.; Kaufman, Samuel R.; Borza, Tudor; Yan, Phyllis; Herrel, Lindsey A.; Miller, David C.; Luckenbaugh, Amy N.; Skolarus, Ted A.; Shahinian, Vahakn B.
Abstract : Introduction: : Accountable care organizations have the potential to increase the value of health care by improving population health and enhancing financial stewardship. How practice context modifies effects on a specialty focused disease, such as prostate cancer care, has implications for their success. Methods: : We performed a retrospective cohort study of newly diagnosed men with prostate cancer between 2012 and 2013 using national Medicare data. Practice affiliation (small single specialty, large single specialty, multispecialty groups) and accountable care organization alignment were measured at the patient level. Generalized linear multivariable models were fitted to derive adjusted rates of treatment and spending for the 12‐month period after diagnosis according to accountable care organization alignment and practice affiliation. Results: : Of 15, 640 patients with newly diagnosed prostate cancer 1, 100 (7.0%) were aligned with accountable care organizations. Patients in these organizations had use of curative treatment similar to that of those not in accountable care organizations (71.4% vs 70.0%, respectively, p=0.33), which did not vary with practice affiliation (p=0.39). Adjusted spending was higher among patients in accountable care organizations ($20, 916 vs $19, 773, p=0.03). However, this relationship was independent of practice affiliation (p=0.90). Higher accountable care organization penetration within a practice was associated with increased spending (p <0.05) but not with treatment (p=0.87). Conclusions: : Patients with prostate cancer aligned with accountable care organizations had similar rates of treatment but increased spending in the year after diagnosis. These findings were similar across practice affiliations. Better specialist engagement by accountable care organizations may be necessary for them to alter practice patterns for specialty care.